POLITISASI LINGKUNGAN OLEH AKTOR PERHUTANI DALAM KASUS KOPERASI TAMBANG INDONESIA III DI KABUPATEN MALANG, JAWA TIMUR - Genta Mahardhika Rozalinna; Lutfi Amiruddin (Jurnal Kawistara, 2018)
The existence of mining industry namely Koperasi Tambang III (KTI III) in Golo beach, Wojo Village, Gedangan, Malang District, brought negative impact socially and ecologically. Unfortunately, State Forestry Company (Perusahaan Umum Kehutanan Negara/Perum Perhutani) was involved to share their land as location of iron sand mining activity. Perhutani, as a State-Owned Enterprises (Badan Usaha Milik Negara/BUMN), has a contradicting roles at the same time, to manage natural resource of the forest and accumulate profit. The aim of this article is to depict the process of politization of environment done by Perhutani, based on dimensions (daily, episodic, and systemic), scales (local and regional), and power networks (local and regional). Through qualitative method with single instrumental case study approach, we find out that Perhutani has been the subject and object of politization by the bigger economic-political power. On three dimensions (daily, episodic, and systemic), we stated there are two configurations of Perhutani’s roles; first, politizing Golo beach through transform Resort Polisi Hutan (RPH). Second, Golo beach has politized by Malang Government as well as KTI III through transforming the Space Planing (Rencana Tata Ruang Wilayah/RTRW). On the local and regional scale, Perhutani seen by the local community and government, has brought not only the job opportunity, but on contrary the ecological damage. On the local power network, Perhutani was the subject to politize local community and government. However, on the divergent side, it was the object of politization done by KTI III and Malang Government.